The Islamic Discourses of Indonesian Islamist Organizations - Chaqoqo, Sri Guno Najib; Ma'mun, Sukron (el Harakah: Jurnal Budaya Islam, 2022)
Several years ago, before HTI was banned in 2017, many terms appeared in the public sphere of Indonesian politics. The terms are; khilafah, Islam kaffah, NKRI with sharia, and great imam (Imam Besar). This article examines the political discourse of Islam in Indonesia used by HTI and FPI. It takes the terms from the media, both their internal and external media. In addition, there are many posters scattered in the news. These terms were mainly taken when the two organizations at that time were still in existence before disbanded. HTI was disbanded in 2018 and FPI in 2020. The purpose of this study is to explore the intent and purpose of these terms. It uses a critical discourse analysis model of Fairclough, Wodak, and van Dick to analyze these terms. The study results indicate that these terms are used to marginalize several popular terms, namely the Unitary State of the Republic of Indonesia (NKRI), the Unitary State of the Republic of Indonesia (NKRI) for the price of death, the 1945 Constitution, and the president. Artikel ini mengkaji bahasa politik Islam di Indonesia yang digunakan oleh HTI dan FPI, yaitu; khilafah, Islam kaffah, NKRI Bersyariah, dan imam besar. Istilah itu diambil dari media-media, baik media internal mereka maupun eksternal. Selain itu juga poster-poster yang banyak bertebaran di dalam pemberitaan- pemberitaan. Istilah-istilah tersebut terutama diambil ketika dua organisasi masa itu masih eksis, sebelum dibubarkan. HTI dibubarkan pada 2018 dan FPI pada 2020. Tujuan dari penelitian ini adalah untuk menelusuri maksud dan sasaran dari istilah-istilah tersebut. Istilah-istilah tersebut akan dibedah dengan menggunakan analisa wacana kritis model Fairclough, Wodak, dan van Dick. Hasil penelitian menunjukkan bahwa istilah-istilah itu digunakan untuk meminggirkan beberapa istilah popular yaitu Negara Kesatuan Republik Indonesia (NKRI), NKRI Harga Mati, Undang-Undang Dasar 1945, dan presiden.